Resposta diferencial de progênies de feijoeiro à eficiência no uso da água - Lima, Dayane Cristina (2016)
With this work we intended to evaluate common bean progenies for grain yield and water use efficiency; verify if the selection in condition without water stress reflects the selection that would be practiced under stress. For this, 80 progenies of the population from BRSMG Talismã x G4280 cross, 80 progenies of the population from BRSMG Talismã x G6492 cross and nine controls were evaluated in contiguous experiments, with high (ADA) and low (BDA) water availability in Lavras and Patos de Minas, MG, in the years 2014 and 2015.The experimental design was 13 x 13 triple lattice with plots of one two-meter row and spaced 0.5m apart. The traits considered in the evaluation were grain yield and water use efficiency (EUA).It was estimated genetic variance, heritability, accuracy, gain expected from selection, correlated response to selection, genetic correlation between ADA and BDA,genetic correlation between the two character evaluated and risk index in the recommendation (IR). The study concluded that the progenies had distinct responses to applied water levels, being possible to identify progenies with high grain yield and EUA; the two conditions of evaluation were equally efficient in the selection, as can be verified by estimates of expected gains with selection, which were always high, as BDA as ADA; progenies differed in risk of their recommendation (IR). Some progenies had IR close to zero, that is, they are tolerant in BDA and responsive under conditions of greater water availability, which is highly desired.